Pre-Wedding Photography as a Semiotic Artifact in Muslim Visual Culture: Hadith Hermeneutics at the Intersection of Textual Authority, Contextual Praxis, and Islamic Ethics - Encep, Encep; Abdurahman, Abdurahman; Mahrima, Sari Tasya; Fauzan, Muhammad Nuril; Jalhani, Ahmad Barakati (JURNAL INDO-ISLAMIKA, 2025)
This study examines the normalization of prewedding photography among urban Indonesian Muslims as visual culture serving aesthetic documentation, social status display, and love expression, while negotiating tensions with Islamic norms (khalwat, ikhtilath, tabarruj) derived from hadiths. Using maqāṣid al-syarī'ah and qualitative textual-cultural analysis, the research reframes prewedding practices not merely as Shari'ah violations but as spaces for reconciling religious authority and societal realities. Findings reveal adaptations like modest attire, non-physical poses, and sessions post-akad (marriage contract), reflecting “cultural ijtihad” to ethically reinterpret hadiths within digital visual culture. The study repositions hadiths as flexible ethical tools guiding Muslims to preserve honor (ḥifẓ al-’irdh) and marital spirituality (ḥifẓ al-dīn), transforming prewedding into expressions of Islamic values. It concludes that maqāṣidī-driven reinterpretation fosters harmony between popular culture and religious norms, advancing social hadith hermeneutics and Islamic visual ethics to address modernity’s challenges. This approach enables Muslims to navigate evolving traditions while upholding theological commitments through contextual adaptability.